Can Positive Framing Reduce Nocebo Side Effects? Current Evidence and Recommendation for Future Research - Barnes, Kirsten; Faasse, Kate; Geers, Andrew L.; Helfer, Suzanne G.; Sharpe, Louise; Colloca, Luana; Colagiuri, Ben (Frontiers in Pharmacology, 2019)
Although critical for informed consent, side effect warnings can contribute directly to poorer patient outcomes because they often induce negative expectations that trigger nocebo side effects. Communication strategies that reduce the development of nocebo side effects whilst maintaining informed consent are therefore of considerable interest. We reviewed theoretical and empirical evidence for the use of framing strategies to achieve this. Framing refers to the way in which information about the likelihood or significance of side effects is presented (e.g. negative frame: 30% will experience headache vs positive frame: 70% will not experience headache), with the rationale that positively framing such information could diminish nocebo side effects. Relatively few empirical studies (k=6) have tested whether framing strategies can reduce nocebo side effects. Of these, four used attribute framing and two message framing. All but one of the studies found a significant framing effect on at least one aspect of side effects (e.g. experience, attribution, threat), suggesting that framing is a promising strategy for reducing nocebo effects. However, our review also revealed some important open questions regarding these types of framing effects, including, the best method of communicating side effects (written, oral, pictorial), optimal statistical presentation (e.g., frequencies versus percentages), whether framing affects perceived absolute risk of side effects, and what psychological mechanisms underlie framing effects. Future research that addresses these open questions will be vital for understanding the circumstances in which framing is most likely to be effective.